Innovation, Impacts and Future Direction of Sustainable Universities: The Case of the University of Minho - Portugal (Braga-Guimarães) - Bandeira Miguel Sopas M; Lobão Ricardo J.A.S (Journal of Sustainability Perspectives, 2023)
Human wellbeing is closely linked to the health of the environment. Around the world, 24% of deaths can be traced back to avoidable environmental factors, according to the World Health Organization. People need clean air to breathe, fresh water to drink, and places to live that are free of toxic substances and hazards. As we begin to experience the long-term consequences of exponential industrial growth and energy use, we must act to reverse these effects and prevent further damage, ensuring we have healthy places to live for generations to come. Objectives of this work are to show the implementation in our University of methods of water and waste management, since early 2017.